Faktor-Faktor yang Mempengaruhi Ketimpangan Ekonomi Kabupaten/Kota di Provinsi Jambi - Almizan; Santo; Irsadunas (Jurnal Informatika Ekonomi Bisnis, 2024)
This research is entitled Factors Influencing District/City Economic Inequality in Jambi Province in 2015-2018. This study aims to analyze the effect of Agglomeration, Labor, and Investment on Regency/City Economic Inequality in Jambi Province in 2015-2018. The analytical method used in this study is panel data regression for the 2015-2018 period which comes from the Jambi Central Bureau of Statistics. Statistical testing includes Common, Fixed, and Random tests, as well as conducting the Chow Test and Hausman Test to obtain the test to be selected. The results of the data analysis show that among the three agglomeration variables (X1) it has a sig. (0.040) < (0.05), so it partially has a significant effect on economic inequality in Jambi Province in 2015-2018. Labor variable (X2) has a sig. (0.8846) (0.05), so partially it has no significant effect on economic inequality in Jambi Province in 2015-2018. Investment (X3) Investment (X3) has a sig. (0.407) (0.05), so partially it has no significant effect on economic inequality in Jambi Province in 2015-2018. Simultaneously obtain a calculated F value of 4.460 with a Probability value (Prob F-statistic) of 0.000. Because the probability value is 0.000 <0.05 (α) and F count (358.6774) > F table (2.78), it can be concluded that all independent variables namely agglomeration, number of workers, investment together have a significant effect on economic inequality in Jambi Province from 2015 to 2018. Based on the value of the coefficient of determination, the independent variables in the equation, namely agglomeration, labor, and investment jointly affect 65.9% of economic inequality in Jambi Province in 2015-2018, while the remaining 24.1% is explained by other factors outside the model.